Currency devaluation and a company's financial structure : a case study. - Lee, David Seng Quee. (2009)
Currency devaluation is considered an exogenous policy change engineered by the authorities. Indonesia is the only country in this region to have experienced so many devaluations over a short period of time. It uses devaluation as an economic tool to stabilize the economy. The effects of utilizing such a tool are felt across the entire economy, both in the macroeconomics as well as the microeconomics of the nation.